SIMULASI PEMETAAN PERODUK PERTANIAN PERDIODE TANAM JANUARI HINGGA MARET DESA BARU TAHAN KABUPATEN SUMBAWA MENGGUNAKAN DIAGRAM SANKEY: Bahasa Indonesia - Shafwan Shafwan (The Journal of Teknologi Pangan, 2022)
Sumbawa Regency is a fairly large area. Agricultural products are one of the strengths of the district. So, in this study, data analysis on the potential of agricultural products was carried out and mapped the potential of agricultural products as well assimulation of production and consumption lines in Baru Tahan Village, Sumbawa Regency. Based on the results of the study, it was obtained data that the total productionof up to 330,600 kg during the period of the study. Based on the paddy produced, 302,600 kg of paddy were sold intact. While 26,250 kg of the production is consumed. The rest isbolted as rice seedlings again, which is 1750 kg. Meanwhile, to increase the selling value, 302,600 kg was modified first with a 5 kg packing process. The existence of an additional process like this can provide added value by increasing the price of rice from Rp. 8,000/kg to Rp. 13,000/kg. In corn products, the process of making corn flour is carried out first in order to increase the selling value. The resulting corn flour product is about 5,000 kg. This innovation can increase the selling value of corn from IDR 5,000 to IDR 57,000. In addition, the process of making tomato sauce is carried out for 5,000 kg of tomatoesbefore being sold. So that this innovation can increase the price of tomatoes from Rp. 2,000/kg to Rp. 15,000/kg. For green beans itself, the process of making 2,000 kg of greenbean juice is carried out.